Role of microbiota in urban life's well-being - Okvitawanli, Ayu (Psychological Research on Urban Society, 2022)
The human beings have evolved together with microbes and are continuously exposed to diverse microbiota. A healthy gut flora promotes health and affords robust immune system, which is often advertised by probiotic supplements. These probiotics promises to build and restore gut flora health. Researches elucidate that gut bacteria are indispensable for our digestive system, and directly influence our moods, our weight, and our perception of the world. We discuss how urbanization possibly disturbs the symbiosis between microbiota and the human beings which leads to a negative impact on health. This review article summarized the previously reported studies and examines the role of microbiota in moods and well-being of urban population, specifically to anxiety and depression. Further, we identify the lacunae in the present research and advise the possible research methods to pursue for further understanding of the role microbiota population has on well-being.